2017
DOI: 10.18052/www.scipress.com/ilns.62.20
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Habitat Assessment of Mount Malindawag Naawan, Misamis Oriental, Philippines

Abstract: Abstract.Habitat fragmentation results to displacement of inhabiting floral and faunal species. The resulting geographic isolation of various species affect regeneration, genetic flows and recruitment. Hence, a study was conducted in a forested area of Mt. Malindawag in Naawan, Misamis Oriental. Sampling stations were designated at the agro-forest, mid-forest and upper-forest habitat types. Species characterizations were based on DAO 2007-01 and IUCN Red List for conservation status. Results showed highest div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
0
0
Order By: Relevance
“…The other is positive associations (R 2 = 6.11) with strong relationships (IO = 0.83; ID = 0.81; IJ = 0.69) which found in HBGMS (Bembab mountain forest). This finding suggests that the relationship is not always exclusive to one form, either positive or negative, which is in line with Canastares et al (2017) that reported similar results. Pratama et al (2012) explained that negative associations show no tolerance for co-living in the same area or the absence of mutually beneficial relationships.…”
Section: Diversity Of Vegetation Coexisting With Merbausupporting
confidence: 92%
“…The other is positive associations (R 2 = 6.11) with strong relationships (IO = 0.83; ID = 0.81; IJ = 0.69) which found in HBGMS (Bembab mountain forest). This finding suggests that the relationship is not always exclusive to one form, either positive or negative, which is in line with Canastares et al (2017) that reported similar results. Pratama et al (2012) explained that negative associations show no tolerance for co-living in the same area or the absence of mutually beneficial relationships.…”
Section: Diversity Of Vegetation Coexisting With Merbausupporting
confidence: 92%
“…Very few studies were made after Merrill, particularly on Annonaceae. Floristic studies accross the country are available (De Guzman et al 2014;Castañares et al 2017;Malabrigo et al 2017;Lillo et al 2018;Ordas et al 2019;Suba et al 2019;Paclibar and Tadiosa 2020;Moran et al 2020;Batuyong et al 2020;Biag and Alejandro 2021;Batuyong et al 2021;Biag and Alejandro 2021;Cordero and Alejandro 2021). Results of these inventories were general listings of different plant families, their distribution, ecology and conservation status.…”
Section: Introductionmentioning
confidence: 99%